CD68 expression is a discriminative feature of indolent cutaneous CD8‐positive lymphoid proliferation and distinguishes this lymphoma subtype from other CD8‐positive cutaneous lymphomas. (1st June 2015) - Wobser, M.; Roth, S.; Reinartz, T.; Rosenwald, A.; Goebeler, M.; Geissinger, E.
Summary: Background: Indolent cutaneous CD8+ lymphoid proliferation is a recently described rare entity among cutaneous T‐cell lymphomas that typically presents with solitary skin lesions at acral sites. Separation from otherwise aggressive T‐cell lymphomas bearing a cytotoxic CD8+ phenotype is fundamental to avoid unnecessary harmful treatment. However, up to now, no reliable discriminative marker has been identified. Objectives: Motivated by these diagnostic quandaries, we have analyzed a large series of archived formalin‐fixed paraffin‐embedded (FFPE) specimens of atypical CD8+ cutaneous infiltrates with clear‐cut diagnosis and clinical follow‐up ( n = 44) including five cases of indolent CD8+ lymphoid proliferation by using immunohistochemistry with the aim of obtaining markers predictive of subtype assignment. Results: We identified exclusive expression of CD68 by lymphoma cells within the subgroup of indolent CD8+ lymphoid proliferation (5/5 cases). Specific CD68 expression in this entity was confirmed by the application of several monoclonal antibodies (KP1, PG‐M1, KiM1P) against the CD68 molecule available for FFPE tissue. In contrast, none of the infiltrates of the other CD8+ cutaneous lymphoma entities stained positive for CD68 (0/39). Conclusions: Based on these observations, we suggest CD68 as a new discriminative marker which is helpful in distinguishing indolent CD8+ lymphoid proliferation from other CD8+ cutaneous lymphomas in ambiguous cases.